STRATEGI DINAS PENDIDIKAN KOTA PONTIANAK DALAM DISTRIBUSI GURU DI KOTA PONTIANAK - Yollanda Sari E.01108092 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This thesis in the title “ Strategi Dinas Pendidikan Kota Pontianak Dalam Distribusi Guru di Kota Pontianak ” has the aim to know how the strategy of education departement of Pontianak to distribute teachers in Pontianak. The background of the thesis is about problems of the amount interest to teaching in the city, many teachers in the village who want to teaching in the city while the number of teachers in the city is excess for the junior high school. Result of the research indicate that distribution of the junior high school teacher is conducted by the education departement is not optimal. Junior high school teacher system and subject teacher, so there was a buildup of some teacher for the same subject. Communication both of the education departement of Pontianak and education departement of province is not still going well, it is seen from the overlap both of the decision taken by the education departement of province and education departement Pontianak. This research is conducted with descriptive research method to know the description how the alternative strategy education departemen of Pontianak for distribution teacher was conducted in December 2012 to June 2013 in the education departemen of Pontianak with the target is junior high school teachers.To realize the equal of quality education is the vision of education departemen of Pontianak. So, to secure the quality of education is needed the policy and the strategy of teacher distribution to get over the issue of inequalityKeywords: strategy, education departement, teacher distribution.